Kansei Engineering Method Survey Paper In Designing And Implementing Market Needs - Parman, Suhadi; Perdana, Dadan; Kurniawan, Sena; Juanda, Riski (Green Publisher Indonesia, 2022)
The appearance and design of the application was originally developed on the basis of its function and usability, as the development of the appearance of an application began to involve many aspects, including from the side of the user's feelings. In the journal survey, this paper discusses the journals that underlie the research using the Kansei Engineering method. Kansei Engineering itself is a design method that uses user feelings in making product designs. The method used in the research is literature study, where the existing data becomes information that is easy to understand and useful. The process of finding sources that are used as literature studies by browsing scientific books or articles from websites such as google scholar to get a journal index indexed by google scientists and the google.com search engine to get journal sources that are sometimes not indexed by google scholar Determination of an adequate number of respondents, complete analysis stages, recommendation metrics supported by the display of appropriate prototypes and specimens will produce optimal research results. Based on the results of the study, it can be concluded that 1. All surveyed papers have similarities in the results of the research in the form of a recommendation matrix that can be applied in making website-based applications and the method used is Kansei Engineering Type I. In terms of analyzing the results of the questionnaire, there are 2 journals that use multivariate analysis with the stages of Coefficient Correlation Analysis (CCA), Principal Component Analysis (PCA), Factor Analysis (FA), and Partial Least Square (PLS). While the other 3 each use different stages. Based on the results of the survey on each paper, it can be concluded that each paper has its own advantages and disadvantages, so that no one is included in the ideal category, such as the number of respondents involved in the study, the number of which is significant with a complete analysis stage. It is also important to display the prototype design to ensure the research results are as expected. For specimens can be adjusted to the needs.